Climate change, rural livelihoods and ecosystem nexus: forest communities in agro-ecological zones of Nigeria (2021)
A top-bottom approach where local problems are treated in isolation has proven ineffective in achieving sustainable development. The need for inclusive approaches to managing the demand for arable lands, forest resources, and the problems of resource exploitation and climate change calls for local understanding of these elements’ interrelationship. Understanding the interrelationships among climate change, agriculture, and the ecosystems in different agroecological zones in Nigeria was the purpose of this chapter. Deforestation and forest degradation analysis approach was utilized. One state and two forest communities from each of the rainforest, savannah, and mangrove agroecological zones were purposively focused in this chapter based on forest distribution and cover. Focus group discussions involving 252 male and female farmers using 30 years as reference were used to garner relevant information. Climate variation caused a slight modification in cropping schedules of farmers due to prolonged dry season, mainly in the savannah region. Farmers engaged in mixed farming and also cultivate more hardy crops like cassava in response to climate uncertainties. Especially in the mangrove and savannah, ecosystem components such as agriculture and population showed increasing trends over the years as forest cover reduces. Downward trend in charcoal production was limited to mangrove and rainforest zones as fishing and hunting becomes vulnerable livelihoods across the zones. The degree and progression of climate change effects on the ecosystem in Nigeria agroecological zones is largely comparable and have both desirable and adverse livelihood outcomes. Affordable insurance policy, credit, agri-inputs, favorable forest regulatory framework, and youth empowerment supports would enhance sustainable adjustment to climate change.